Indium tin oxide film and preparation method and application thereof

By preparing an indium tin oxide film with a specific crystal surface structure by sputtering method on the substrate surface, the problems of high visible light transmittance, good conductivity and low near-infrared transmittance in applications are solved, and the adhesion and mechanical properties of the film are improved.

CN119859785APending Publication Date: 2025-04-22BAIMTEC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795270.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In applications with high functional requirements, it is difficult to take into account the problems of high visible light transmittance, good conductivity and low near-infrared transmittance, and it is easy to fall off the substrate in applications.

Method used

By preparing an indium tin oxide film by sputtering method on the substrate surface, it is ensured that the X-ray diffraction image of the film layer includes both (222) crystal plane, (400) crystal plane, (441) crystal plane and (622) crystal plane, thereby optimizing the mechanical properties and surface characteristics of the film.

Benefits of technology

It realizes high hardness, good adhesion, low surface roughness, good conductivity, high visible light transmittance and low near infrared transmittance of the ITO film, and has excellent overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859785A_ABST
    Figure CN119859785A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of indium tin oxide films, in particular to an indium tin oxide film and a preparation method and application thereof, and an X-ray diffraction image of the indium tin oxide film comprises a crystal face (222), a crystal face (400), a crystal face (441) and a crystal face (622). The mechanical properties of the ITO film, such as hardness and elastic modulus, are relatively excellent; the surface roughness of the ITO film is relatively low, and the surface flatness of the ITO film is high; the film layer is good in quality, relatively high in adhesive force to a substrate and not easy to fall off from the substrate during application; the ITO film has good conductivity, high visible light transmittance, low near-infrared region transmittance and excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of indium tin oxide films, and in particular to an indium tin oxide film and a preparation method and application thereof. Background Art

[0002] Indium tin oxide (ITO) film is a semiconductor transparent oxide film material. Currently, ITO film materials are widely used in windshield surfaces, mobile phones and tablets, solar cells and other fields. With the development of science and technology, the functional requirements for ITO films are getting higher and higher.

[0003] Therefore, it is crucial to develop an ITO film with high visible light transmittance, good conductivity and low near-infrared transmittance, and the ITO film is not easy to fall off from the substrate during application. Summary of the invention

[0004] In view of the above problems, the present application provides an indium tin oxide film and a preparation method and application thereof. The mechanical properties of the ITO film, such as hardness and elastic modulus, are relatively excellent; the surface roughness and surface flatness of the ITO film are relatively high, the film layer quality is good, the adhesion to the substrate is relatively high, and it is not easy to fall off from the substrate during application; the ITO film has good conductivity, high visible light transmittance and low near-infrared transmittance, and has excellent comprehensive performance.

[0005] In a first aspect, the present application provides an indium tin oxide film, wherein an X-ray diffraction (XRD) image of the indium tin oxide film includes a (222) crystal plane, a (400) crystal plane, a (441) crystal plane, and a (622) crystal plane.

[0006] In the technical solution of the implementation mode of the present application, the indium tin oxide film has four crystal planes at the same time in the XRD image, so that the mechanical properties of the ITO film, such as hardness and elastic modulus, are relatively excellent; the surface roughness of the ITO film is relatively low, and its surface flatness is high; the film layer has good quality, high adhesion to the substrate, and is not easy to fall off from the substrate during application; at the same time, the ITO film has good conductivity, high visible light transmittance and low near-infrared transmittance, and has excellent comprehensive performance.

[0007] In the present application, the XRD pattern can be obtained by using an instrument or method known in the art. For example, the XRD pattern is obtained by using a Bruker D8A A25 X-ray diffractometer, and the test process is as follows:

[0008] (1) Sample preparation: Cut a 10 mm × 10 mm film sample and place it in the instrument;

[0009] (2) Instrument debugging: Turn on the X-ray diffractometer and adjust the X-ray tube voltage, current and other parameters to ensure stable operation of the instrument;

[0010] (3) Parameter setting: according to the characteristics of the sample, set the scanning range (10-80°) and step size (0.05° / step, 0.1 s / step);

[0011] (4) Data acquisition and processing: Start scanning, and the instrument automatically records the position, intensity and other information of the diffraction peak, and processes the diffraction data, including background subtraction, peak position correction, peak shape fitting, etc., to obtain the XRD image.

[0012] In the present application, indium tin oxide (ITO), also known as tin-doped indium oxide, is a transparent conductive oxide (TCOs) material. As an example, the indium tin oxide is composed of 90 wt% indium trioxide (In2O3) and 10 wt% tin dioxide (SnO2).

[0013] Preferably, the intensity ratio of the diffraction peaks corresponding to the (222) crystal plane, (400) crystal plane, (441) crystal plane and (622) crystal plane is (0.1-0.8):1:(0.05-0.8):(0.05-0.5); further preferably (0.4-0.6):1:(0.3-0.6):(0.3-0.4); wherein, 0.1-0.8 may be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, etc.; 0.05-0.8 may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, etc.; 0.05-0.5 may be 0.1, 0.2, 0.3, 0.4, etc.; the intensities of the diffraction peaks corresponding to different crystal planes may be the same or different.

[0014] Preferably, the surface roughness of the indium tin oxide film is ≤2.5nm, more preferably ≤2.1nm; further preferably ≤0.6-2.1nm, for example 0.2nm, 0.4nm, 0.6nm, 0.8nm, 1nm, 1.2nm, 1.4nm, 1.6nm, 1.8nm, 2nm, 2.2nm, 2.4nm, etc.

[0015] In the present application, the surface roughness can be tested by methods known in the art. As an example, a laser microscope method is used, wherein the probe model used is OTESPA-R3, the instrument model of the atomic force microscope is Bruker Dimension Icon, the intelligent scanning mode is set, the scanning speed is 1 Hz, the resolution is 256×256, and the scanning area is 3×3 μm to collect images, process data, and calculate the surface roughness Ra.

[0016] Preferably, the adhesion of the indium tin oxide film is ≥3 mN, more preferably 3-11 mN, and even more preferably 5-11 mN, for example 4 mN, 5 mN, 6 mN, 7 mN, 8 mN, 9 mN, 10 mN, 11 mN, 12 mN, etc.

[0017] In the present application, the adhesion can be tested by methods known in the art. As an example, the test method is a scratch test method; the process is as follows: a nanoindenter model Hysitron Ti950-Triboindenter is used to test the adhesion between the sample substrate and the film; specifically, the indenter in the nanoindenter relies on the probe to slowly approach the sample surface to confirm the sample test height; the indenter surface is used to uniformly increase the load on the sample surface film by moving forward in parallel (moving rate is 10 μm / s; moving distance is 250 μm, thermal drift rate is 0.157 nm / s), and the indenter surface is used to relatively scratch the sample surface film uniformly. According to the relevant data of the change of normal force over time, it can be seen that the normal force gradually increases in a linear manner in the early stage, and the normal force increases or decreases irregularly in the later stage, and the normal force when it first decreases is used as the adhesion.

[0018] Preferably, the resistivity of the indium tin oxide film is ≤10 -3 Ω·cm, more preferably (5-8)×10 -4 Ω·cm, for example 5×10 -4 Ω·cm、6×10 -4 Ω·cm、7×10 -4 Ω·cm, etc.

[0019] In the present application, the resistivity can be tested by a method known in the art. As an example, the test method is a four-probe method, and the model of the four-probe used is NAGY SD-810.

[0020] Preferably, the average transmittance of visible light of the indium tin oxide film is ≥60%, more preferably ≥85%, for example, 60%, 70%, 75%, 80%, 85%, 90%, 95%, etc.

[0021] In the present application, the wavelength range of visible light is 380-780 nm; the wavelength range of near infrared region is 780-2400 nm.

[0022] In this application, the average transmittance of visible light and the average transmittance in the near-infrared region can be tested by methods known in the art. As an example, a spectrophotometer model UH4150 Hitachi (HITACHI) is used for testing, and a measurement mode such as transmittance is selected according to the test item; if the average transmittance of visible light is tested, the measurement wavelength range is set to 380-780nm, and the measurement mode is transmittance. After testing, a series of visible light transmittances are obtained, and the transmittances of each wavelength measured are added, and then divided by the number of wavelengths to obtain the average transmittance; the same applies to the remaining items.

[0023] Preferably, the average transmittance of the indium tin oxide film in the near-infrared region is ≤81%, further preferably 60%-77%, for example 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, etc.

[0024] Preferably, the thickness of the indium tin oxide film is ≥250 nm, optionally 350-500 nm, for example, 300 nm, 350 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, etc.

[0025] In a second aspect, the present application provides a method for preparing an indium tin oxide film, the method for preparing an indium tin oxide film comprising the following steps:

[0026] Indium tin oxide is disposed on the surface of the substrate by sputtering to obtain an indium tin oxide film;

[0027] The X-ray diffraction image of the indium tin oxide film includes a (222) crystal plane, a (400) crystal plane, a (441) crystal plane, and a (622) crystal plane.

[0028] Preferably, the sputtering method includes magnetron sputtering.

[0029] Preferably, the sputtering temperature is 10-40°C, such as 15°C, 20°C, 25°C, 30°C, 35°C, etc.

[0030] In the technical solution of the implementation mode of the present application, the sputtering temperature is relatively low and can be completed at room temperature without the need for additional heating operations, thus saving energy; and the ITO film prepared at a relatively low temperature has excellent comprehensive performance.

[0031] Preferably, the sputtering is performed in an inert gas and oxygen.

[0032] As an example, the inert gas includes argon.

[0033] In the present application, the inert gas and oxygen are high-purity gases (≥99.99%).

[0034] Preferably, the volume flow rate of the inert gas is 20-100 sccm, for example, 40 sccm, 60 sccm, 80 sccm, etc.

[0035] Preferably, the volume flow rate of the oxygen gas is 1-10 sccm, for example, 2 sccm, 4 sccm, 6 sccm, 8 sccm, etc.

[0036] Preferably, the volume flow ratio of the inert gas to oxygen is 100:(10-15), wherein 10-15 can be 12, 14, etc.

[0037] In the technical solution of the implementation mode of the present application, the ratio of the volume flow rates of the inert gas and oxygen is within the above range. The reason is that the oxygen content will directly affect the resistance and visible light transmittance of the ITO film; if the ratio of the volume flow rates of the two is too small, the oxygen content will be too small, resulting in low resistance and low transmittance; if the ratio of the volume flow rates of the two is too large, the oxygen content will be too large, resulting in high resistance and high transmittance.

[0038] Preferably, the sputtering working gas pressure is ≤0.1Pa, such as 0.05Pa, 0.01Pa, etc.

[0039] Preferably, the sputtering time is 10-100 min, for example, 20 min, 40 min, 60 min, 80 min, etc.

[0040] In the present application, the power source used for sputtering is a DC pulse power source, and its reversal time output within a working square wave cycle is a negative voltage, the main function of which is to neutralize the positive ions on the target surface and improve the coating quality.

[0041] Preferably, the sputtering power source has a power of 100-200 W, such as 120 W, 140 W, 160 W, 180 W, etc.

[0042] Preferably, the power reversal time of the sputtering is 0.4-4 μs, optionally 1-3 μs, such as 0.5 μs, 1 μs, 2 μs, 3 μs, 3.5 μs, etc.

[0043] In this application, the power reversal time refers to the time for maintaining a negative voltage output at a certain frequency.

[0044] In the technical solution of the implementation mode of the present application, the power reversal time is within the above range. The reason is that: the power reversal time will neutralize the positive ions on the target surface; if the power reversal time is too short, the positive ions will not be completely neutralized, affecting the crystal growth; if the power reversal time is too long, negative ions will remain on the target surface, affecting the crystal growth.

[0045] Preferably, the sputtering power supply frequency is 5-100 kHz, optionally 5-20 kHz, for example, 5 kHz, 10 kHz, 15 kHz, 20 kHz, 40 kHz, 60 kHz, 80 kHz, etc.

[0046] Preferably, the power density of the sputtering is 3-4 W / cm 2 , for example 3W / cm 2 、3.5W / cm 2 , 4W / cm 2 wait.

[0047] As an example, the present application adopts an ITO ceramic target for magnetron sputtering, wherein the distance between the target and the substrate is between 90-110 mm.

[0048] Preferably, the process further includes cleaning the substrate before sputtering.

[0049] In the present application, the cleaning of the substrate may be performed by methods known in the art. As an example, two cleaning steps may be performed, wherein the first cleaning step includes solvent wiping and the second cleaning step includes ion source magnetron sputtering.

[0050] As an example, the solvent used for the first cleaning includes any one of isopropyl ketone, petroleum ether or water, or a combination of at least two of them.

[0051] As an example, the first cleaning may also include wiping with a cleaning brush such as a steel wool.

[0052] As an example, the first cleaning also includes drying.

[0053] As an example, the second cleaning is performed in an inert gas such as argon.

[0054] As an example, the operating voltage of the ion source in the second cleaning is 2900-3000V, such as 2920V, 2940V, 2960V, 2980V, etc.

[0055] In a third aspect, the present application provides an indium tin oxide film as described in the first aspect, or an indium tin oxide film obtained by the preparation method as described in the second aspect, and its use in a windshield, an electronic product or a solar cell.

[0056] Compared with the prior art, this application has at least the following beneficial effects:

[0057] (1) The mechanical properties of the ITO film described in the present application, such as hardness and elastic modulus, are relatively excellent; the surface roughness and surface flatness of the ITO film are relatively high, the film layer has good quality, high adhesion to the substrate, and is not easy to fall off from the substrate during application; the ITO film has good conductivity, high visible light transmittance and low near-infrared transmittance, and has excellent comprehensive performance.

[0058] (2) The thickness of the ITO film described in this application is 377-500 nm; the resistivity is (5.3-8.0)×10 -4 Ω·cm, the adhesion is 5.1-10.9mN; the average transmittance of visible light is 85.0%-90.7%, and the average transmittance in the near-infrared region is 66.8%-76.1%.

[0059] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0061] Figure 1 is a scanning electron microscope image of Example 1;

[0062] Figure 2 is a scanning electron microscope image of Example 2;

[0063] Figure 3 is a scanning electron microscope image of Example 3;

[0064] Figure 4 is a scanning electron microscope image of Example 4;

[0065] Figure 5 XRD diagrams of some embodiments of the present application;

[0066] Figure 6 This is a graph of average transmittance of visible light in some embodiments of the present application;

[0067] Figure 7 This is a graph of average transmittance in the near-infrared region of some embodiments of the present application. DETAILED DESCRIPTION

[0068] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0070] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0071] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" are listed in this document, and "2-10" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0072] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0073] Example 1

[0074] This embodiment provides an ITO film, which is prepared by the following method:

[0075] (1) Preparation of 10×10 cm 2 Inorganic glass: Use isopropyl acetone to wipe the inner and outer surfaces of inorganic glass, petroleum ether to wipe the inner and outer surfaces of inorganic glass, steel wire cloth to wipe the inner and outer surfaces of inorganic glass, deionized water to wipe the inner and outer surfaces of inorganic glass, petroleum ether to wipe the inner and outer surfaces of inorganic glass, and dry it in an oven;

[0076] (2) The inorganic glass is placed in a vacuum chamber, and the chamber is evacuated to 0.003 Pa, which is the background vacuum; high-purity argon gas is introduced to magnetron sputter the surface of the inorganic glass using an ion source, and the working voltage of the ion source is 2900 V, so as to perform secondary cleaning on the surface of the inorganic glass;

[0077] (3) introducing argon gas at 100 sccm and pre-sputtering the ITO ceramic target for 5 min to remove impurities on the target surface;

[0078] (4) At room temperature (20°C), argon gas 50 sccm and oxygen 6 sccm were introduced, and the inorganic glass surface was magnetron sputtered using an ITO ceramic target. The working gas pressure was adjusted to 0.1 Pa, the DC pulse power was 140 W, the power reversal time was 0.4 μs, the power frequency was 5 kHz, and the power density was 3.5 W / cm 2 , sputtering for 60 minutes to obtain ITO thin film.

[0079] Examples 2-14 and Comparative Example 1

[0080] Except for the parameters mentioned in Table 1, an ITO film was prepared according to the method described in Example 1.

[0081] Table 1

[0082]

[0083]

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that after sputtering, the ITO film is heated to 400° C. at a rate of 50° C. / h and kept at that temperature for 3 h. The rest is the same as Example 1.

[0086] Performance Testing

[0087] (1)Thickness:

[0088] (2) Morphology test: The images were observed using a Hitachi SU8010 scanning electron microscope at a magnification of 20,000 times.

[0089] (3) XRD test:

[0090] 1) Sample preparation: Cut a 10 mm × 10 mm film sample and put it into the instrument;

[0091] 2) Instrument debugging: Turn on the X-ray diffractometer and adjust the X-ray tube voltage, current and other parameters to ensure stable operation of the instrument;

[0092] 3) Parameter setting: according to the characteristics of the sample, set the scanning range (10-80°) and step length (0.05° / step, 0.1s / step);

[0093] 4) Data acquisition and processing: Start scanning, the instrument automatically records the position, intensity and other information of the diffraction peak, and processes the diffraction data, including background subtraction, peak position correction, peak shape fitting, etc., to obtain the XRD image.

[0094] (4) Resistivity: The test method is the four-probe method, and the model of the four-probe used is NAGY SD-810.

[0095] (5) Adhesion: The test method is the scratch test method; the process is as follows: a nanoindenter model Hysitron Ti950-Triboindenter is used to test the adhesion between the sample substrate and the film; specifically, the indenter in the nanoindenter relies on the probe to slowly approach the sample surface to confirm the sample test height; a uniform forward movement (movement rate of 10 μm / s; movement distance of 250 μm, thermal drift rate of 0.157 nm / s) is adopted to use the surface of the indenter to uniformly increase the load on the sample surface film to relatively scratch it. According to the relevant data obtained, it can be seen that the normal force gradually increases in a linear manner in the early stage, and then increases or decreases irregularly in the later stage. The normal force at the time of the first decrease is taken as the adhesion.

[0096] (6) Surface roughness: The laser microscopy method was used, where the probe model used was OTESPA-R3, the instrument model of the atomic force microscope was Bruker Dimension Icon, and the intelligent scanning mode was set with a scanning speed of 1 Hz, a resolution of 256 × 256, and a scanning area of ​​3 × 3 μm to collect images, process data, and calculate the surface roughness Ra.

[0097] (7) Hardness and elastic modulus: The indentation method was used for testing, using a Hysitron Ti950-Triboindenter nanoindenter. Specifically, the indenter in the instrument slowly approaches the sample surface with the help of the probe to confirm the sample test height; the indenter is perpendicular to the sample surface, and the indenter presses the sample film surface at a constant speed, vertically, and evenly with increasing load (movement rate of 40 nm / s; pressing depth of 200 nm), and elastic modulus and hardness analysis are performed based on the relevant data obtained. For details, refer to Oliver WC, Pharr G M. Measurement of hardness and elastic modulus by instrumented indentation: Advances in understanding and refinements to methodology [J]. Journal of Materials Research, 2004, 19 (1): 3-20. DOI: 10.1557 / jmr.2004.19.1.3.

[0098] (8) Transmittance: A UH4150 Hitachi spectrophotometer was used for testing. The measurement mode, such as transmittance, was selected according to the test item. If the average transmittance of visible light was tested, the measurement wavelength range was set to 380-780 nm and the measurement mode was transmittance. After testing, a series of visible light transmittances were obtained. The transmittances of each wavelength measured were added together and then divided by the number of wavelengths to obtain the average transmittance. The other items were tested in the same way to obtain the average transmittance of visible light and the average transmittance of the near-infrared region.

[0099] The test results are summarized in Tables 2-4 and Figure 1-7 middle.

[0100] Figure 1 , Figure 2 , Figure 3 and Figure 4 The scanning electron microscope images of the ITO films described in Example 1, Example 2, Example 3 and Example 4 are respectively given, proving that the ITO film is successfully prepared in this application and has a high surface flatness.

[0101] Table 2

[0102]

[0103]

[0104] It should be noted in Table 2 that, in order to facilitate comparison of the intensity relationship between different diffraction peaks, the intensity of the diffraction peak in each embodiment is converted using the intensity of the diffraction peak corresponding to the (400) crystal plane as reference 1.

[0105] As an example, Figure 5 The XRD diagrams of Examples 1-4 of the present application are given, which show that the diffraction peak intensities of different crystal planes of each example are specifically shown in Table 3, and the proportional relationship in Table 2 is calculated based on Table 3.

[0106] Table 3

[0107] (222) crystal face (400) crystal face (441) crystal face (622) Crystal face Example 1 14 42 12 15 Example 2 30 61 21 23 Example 3 33 61 21 23 Example 4 18 117 7 7

[0108] Table 4

[0109]

[0110]

[0111] According to the data in Table 2-Table 4, taking Examples 1-14 as an example, the thickness of the ITO film in this application is 251-628 nm; the resistivity is (4.6-11.6)×10 -4 Ω·cm, adhesion is 3.5-10.9mN, surface roughness is 0.69-2.08nm, hardness is 5.43-13.55GPa, elastic modulus is 59.61-149.02GPa; the average transmittance of visible light is 60.7%-95.7%, and the average transmittance in the near-infrared region is 53.1%-80.7%. The mechanical properties of the ITO film described in this application, such as hardness and elastic modulus, are relatively excellent; the surface roughness of the ITO film is relatively low, and its surface flatness is high; the film layer is of good quality, has high adhesion to the substrate, and is not easy to fall off from the substrate during application; the ITO film has good conductivity, high visible light transmittance and low near-infrared transmittance, and excellent comprehensive performance.

[0112] In the preferred range of the present application, taking Examples 2-3, 6-7, 9-10, and 12-13 as examples, the thickness of the ITO film described in the present application is 377-500 nm; the resistivity is (5.3-8.0)×10 -4 Ω·cm, adhesion is 5.1-10.9mN; the average transmittance of visible light is 85.0%-90.7%, and the average transmittance in the near infrared region is 66.8%-76.1%. The mechanical properties of the ITO film described in this application, such as hardness and elastic modulus, are relatively excellent; the surface roughness of the ITO film is relatively low, and its surface flatness is high; the film layer is of good quality, has high adhesion to the substrate, and is not easy to fall off from the substrate during application; the ITO film has good conductivity, high visible light transmittance and low near infrared transmittance, and excellent comprehensive performance.

[0113] Analysis of Comparative Example 1 and Example 2 shows that the performance of Comparative Example 1 is not as good as that of Example 2. Specifically, the adhesion of Comparative Example 1 is relatively low, the surface roughness is relatively high, and the average visible light transmittance is relatively low, which proves that the ITO film contains (222) crystal plane, (400) crystal plane, (441) crystal plane and (622) crystal plane at the same time, and has better comprehensive performance.

[0114] Combination Figure 6 and Figure 7 ,Analysis of Examples 1-4 shows that the performance of Examples 1 and 4 is not as good as that of Examples 2-3. Specifically, the adhesion of Example 1 is low, and the adhesion and average transmittance of visible light of Example 4 are both low, which proves that in the preparation, when the power reversal time is in the range of 1-3.5μs, the comprehensive performance of the formed ITO film is better.

[0115] The analysis of Examples 5-8 shows that the performance of Examples 5 and 8 is not as good as that of Examples 6-7. Specifically, the resistivity of Example 5 is high, and the resistivity of Example 8 is low, which proves that the power density is 3-4 W / cm 2 Within this range, the formed ITO film has better comprehensive performance.

[0116] Analysis of Examples 11-14 shows that the performance of Examples 11 and 14 is not as good as that of Examples 12-13. The average transmittance of visible light of Example 11 is low and the resistivity is low, while the resistivity of Example 14 is high. This proves that during the preparation, when the volume flow ratio of inert gas and oxygen is in the range of 100:(10-15), the comprehensive performance of the formed ITO film is better.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. An indium tin oxide film, characterized in that: The X-ray diffraction pattern of the indium tin oxide film includes a (222) crystal plane, a (400) crystal plane, a (441) crystal plane, and a (622) crystal plane.

2. The indium tin oxide film according to claim 1, characterized in that The intensity ratio of the diffraction peaks corresponding to the (222) crystal plane, (400) crystal plane, (441) crystal plane and (622) crystal plane is (0.1-0.8):1:(0.05-0.8):(0.05-0.5); further preferably (0.4-0.6):1:(0.3-0.6):(0.3-0.4).

3. The indium tin oxide film according to claim 1 or 2, characterized in that: The surface roughness of the indium tin oxide film is ≤2.5 nm, more preferably ≤2.1 nm; and even more preferably ≤0.6-2.1 nm. Preferably, the adhesion of the indium tin oxide film is ≥3 mN, more preferably 3-11 mN, and even more preferably 5-11 mN; Preferably, the resistivity of the indium tin oxide film is ≤10 -3 Ω·cm, more preferably (5-8)×10 -4 Ω·cm.

4. The indium tin oxide film according to any one of claims 1 to 3, characterized in that: The average visible light transmittance of the indium tin oxide film is ≥60%, and more preferably ≥85%; Preferably, the average transmittance of the indium tin oxide film in the near infrared region is ≤81%, more preferably 60%-77%.

5. The indium tin oxide film according to any one of claims 1 to 4, characterized in that: The thickness of the indium tin oxide film is ≥250 nm, and can be optionally 350-500 nm.

6. A method for preparing an indium tin oxide film, characterized in that: The method for preparing the indium tin oxide film comprises the following steps: Indium tin oxide is disposed on the surface of the substrate by sputtering to obtain an indium tin oxide film; The X-ray diffraction image of the indium tin oxide film includes a (222) crystal plane, a (400) crystal plane, a (441) crystal plane, and a (622) crystal plane.

7. The preparation method according to claim 6, characterized in that: The sputtering method includes magnetron sputtering; Preferably, the sputtering temperature is 10-40°C; Preferably, the sputtering is performed in an inert gas and oxygen; Preferably, the volume flow rate of the inert gas is 20-100 sccm; Preferably, the volume flow rate of oxygen is 1-10 sccm; Preferably, the volume flow ratio of the inert gas to oxygen is 100:(10-15); Preferably, the sputtering working gas pressure is ≤0.1Pa; Preferably, the sputtering time is 10-100 min.

8. The preparation method according to claim 6 or 7, characterized in that: The power of the sputtering power supply is 100-200W; Preferably, the power reversal time of the sputtering is 0.4-4 μs, optionally 1-3 μs; Preferably, the power frequency of the sputtering is 5-100kHz, optionally 5-20kHz; Preferably, the power density of the sputtering is 3-4 W / cm 2 .

9. The preparation method according to any one of claims 6 to 8, characterized in that: The method also includes cleaning the substrate before sputtering.

10. Use of the indium tin oxide film according to any one of claims 1 to 5, or the indium tin oxide film obtained by the preparation method according to any one of claims 6 to 9, in a windshield, an electronic product or a solar cell.